The oldest layer of Amuric-Tungusic lexical contacts - Knapen, Martijn Gerardus Theodorus Maria (Helsingin yliopisto, 2021)
Research on the interaction of the Amuric languages (referred to as “Nivkh” or “Ghilyak” when regarded as a single language) with the Tungusic languages was initiated by Grube (1892). His focus on loanwords has been the object of study until the present day. Recently, Janhunen (2010: 292, 296; 2016: 23) has suggested that contact between the two families already started between their ultimate ancestors: Pre-Proto-Amuric and Proto-Tungusic. This thesis investigates whether some of the lexical parallels proposed by earlier research belong to this period. As the thesis is written from the perspective of language contact, the parallels are regarded as the result of borrowing instead of inheritance. The distinction between these two modes of transmission formed the theoretical basis for the methodology that was employed. To prove ancient contact, it had to be shown that the Amuric and Tungusic languages inherited their shared lexemes from their respective ancestors and that these ancestors may have borrowed from each other. As the methodology relied on the literature on Amuric and Tungusic historical phonology, an overview of this topic is also included. First, fifty parallels were drawn from those listed in previous research. These could be reconstructed to Proto-Amuric and Proto-Tungusic using the Comparative Method and thus could have been inherited from them or an earlier ancestor in the case of Proto-Amuric. Additionally, they exhibited phonological similarities that could reasonably be expected from borrowing between Pre-Proto-Amuric and Proto-Tungusic. Afterwards, a direction of borrowing had to be established, the principal evidence of borrowing. For that purpose, nine criteria were developed. These criteria considered morphology, diachronic and synchronic phonology, extent of attestation, semantics and extra-linguistic factors. Finally, the data was separated into older and younger strata, since in the selection phase only the Proto-Amuric stage was considered, while the target was Pre-Proto-Amuric. These ...